Effectiveness of Transformational Leadership, Motivation, and Job Satisfaction in Improving Teacher Performance at Madrasah Aliyah Riyadhul Jannah Subang - Hasanah, Ru'yatul; Karim, Abdul; Subasman, Iman; Haedari, Amin; Jalaludin , Jalaludin; Zulfahmi, Zulfahmi (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
The quality of human resources is a decisive factor in the success of Islamic educational institutions, yet studies on Islamic transformational leadership and its impact on teacher performance remain limited. This research addresses the gap by examining the role of transformational leadership, work motivation, and job satisfaction in shaping teacher performance at Madrasah Aliyah Riyadhul Jannah Subang, an institution facing challenges of low motivation and high workload among teachers. Using a quantitative survey method, data were collected from 16 teachers and analyzed through regression techniques. The findings indicate that work motivation has a positive and significant effect on teacher performance, while transformational leadership and job satisfaction show no significant effect. This suggests that structural and cultural factors within the madrasah, including workload distribution and institutional norms, may weaken the influence of leadership and satisfaction compared to motivation. The study implies that strengthening teacher motivation is crucial for performance improvement in Islamic education, while leadership approaches must be contextualized to the realities of madrasah culture. These results highlight the need for further exploration of Islamic transformational leadership models in enhancing teacher performance.